Review of the genera Thubana Walker and Torodora Meyrick (Lepidoptera: Lecithoceridae) from Sumatra, Indonesia - Park, Kyu-Tek; Heppner, John B. (Zootaxa, 2023)
Sumatra is the second largest island that is fully within Indonesian territory, but it is one of the most poorly explored areas for species diversity of the family Lecithoceridae, with less than 10 known species. In the present paper, six new species of Thubana Walker, 1864 (T. sumatrana sp. nov., T. spiniosa sp. nov., T. lata sp. nov., T. prapatensis sp. nov., T. siantarensis sp. nov., and T. selenisa sp. nov.) and three new species of Torodora Meyrick (T. diehliella sp. nov., T. exilivalvata sp. nov., and T. squariella sp. nov.) are described from Sumatra. In addition, Thubana ochracea Park & Abang, 2005, which was described from Sarawak, Malaysia, is reported for the first time from Sumatra. Illustrations of adults and genitalia of all new species are given. A list of the known species of the subfamily Torodorinae from Indonesia is provided.